Effect of implementing one way traffic in Kuantan city - Vun, Hon Yuan (2016)
One way traffic system has been implemented in Kuantan City to relieve traffic congestion problem. This study is done to evaluate the effect of implementing one way traffic system along Jalan Tun Ismail. The major objective is to study the traffic volume and pattern after conversion of the road into one way street, as well as to identify problems and issues related to traffic engineering that arose due to the conversion. A total of four surveys have been done on three weekdays and one weekend respectively, to determine traffic volume during peak hours. Traffic volume is recorded by means of manual counting, done by at least three researchers. Traffic volume is recorded according to vehicle classes. The outcome shows that traffic volume has increased significantly, while having smoother traffic flow. Light vehicles are having the highest composition in traffic volume. The major problems identified after implementing one way traffic system include frequent lane cutting of vehicles. One of the major adjustments proposed is to install adequate road signage to aid road users in driving on the road. In conclusion, implementing one way traffic has improved the traffic condition along Jalan Tun Ismail. Proposals have been made to rectify the problems identified on the stretch of road.